Plasma and cerebrospinal fluid levels of cytokines as disease markers of neurologic manifestation in long-term HTLV-1 infected individuals. (8th May 2018) - Rosa, Daniela V; Magno, Luiz A; Pereira, Nathália CM; Romanelli, Luiz C; Albuquerque, Maicon R; Martins, Marina L; de Freitas Carneiro Proietti, Anna B; Nicolato, Rodrigo; Simões e Silva, Ana C; de Miranda, Debora M
Aim: The aim of this study is to evaluate the presence of a particular immunological profile in individuals long-term infected with HTLV-1, followed presenting different clinical courses.Materials & methods: Forty-eight individuals were evaluated for 19 cytokines analyzed in cerebrospinal fluid and plasma of patients with HTLV-1 presenting with and without neurological symptoms.Results: Proinflammatory cytokines and the chemokine ligand 11 (ITAC/CXCL11) were increased in individuals with HTLV-1 coursing with neurological symptoms.Conclusion: Different cytokines' expression profile in the presence of neurological symptoms may help to understand and characterize the progression for severe clinical presentations.